IMPLEMENTASI SISTEM INFORMASI AKADEMIK PADA MADRASAH IBTIDAIYAH - Fiqih Fazriyansyah; Andri Kusmayadi (Tatar Pasundan: Jurnal Diklat Keagamaan, 2023)
This study was conducted to examine how technological advancement, particularly in the area of information technology, has affected academic institutions. This is significant because information technology now permeates all facets of modern civilization and human life. This study used a qualitative methodology and descriptive analysis. The Madrasah Ibtidaiyah is the locus. The information used in the analysis was gathered from the academic information system findings implemented in this madrasah. The outcomes of descriptive analysis have been able to support and facilitate the development of educational programs that bring together all academics, including educators, instructors, support staff, students, parents, and other stakeholders.Keywords: Academic Information System; Madrasah; Ibtidaiyah